â€œCETING ASIKâ€ SEBAGAI UPAYA PENCEGAHAN BALITA STUNTING DI WILAYAH KERJA PUSKESMAS PELABUHAN DAGANG - Sari Gustia Ayu; Haryati Haryati; MZ Fakhrurazi; Meinarisa Meinarisa (Universitas Jambi, 2023)
ABSTRACT Stunting in Indonesia is one of the health problems faced by infants and toddlers. Jambi Province itself has a chronic nutritional problem (stunting) which is of particular concern. Optimal breastfeeding is very important to prevent malnutrition in infants and toddlers. Important interventions in stunting prevention. Interventions on stunting are aimed at improving the nutritional status of infants and toddlers, preventing stunting, especially during the early stages of life. The reason for the low coverage of exclusive breastfeeding in the Pelabuhan Dagang Health Center is that public awareness in encouraging increased breastfeeding is still relatively low. For this reason, an activity was carried out to encourage an increase in exclusive breastfeeding outcomes, namely